The Impact of PBL-Based E-Learning on Critical Thinking and Mathematical Communication in Ethnomathematics-Based Pythagorean Learning - Ayun Rahayu Lestariningsih; Rusijono Rusijono; Fajar Arianto (ARKA INSTITUTE, 2026)
The integration of Problem-Based Learning (PBL) and e-learning represents an instructional approach that has the potential to foster higher-order thinking by actively engaging students in structured problem-solving activities. This study examines the impact of combining e-learning with the PBL model and an ethnomathematics approach on eighth-grade students’ critical thinking and mathematical communication skills in learning the Pythagorean Theorem. A quasi-experimental design with a non-equivalent control group was implemented involving Grade 8 students at SMP Negeri 4 Madiun. Participants were divided into an experimental group, which received ethnomathematics-based PBL supported by e-learning, and a control group, which was taught using conventional instructional methods. Data were collected through pretests and posttests measuring critical thinking and mathematical communication skills, and the differences between groups were analyzed using inferential statistical techniques. The findings reveal that the integration of e-learning within an ethnomathematics-oriented PBL framework has a significant and positive effect on students’ critical thinking and mathematical communication skills, thereby demonstrating its effectiveness in promoting higher-order thinking in mathematics education.